Clinical characteristics of 10 Chinese patients with melorheostosis and identification of a somatic MAP2K1 variant in one case. Issue 10 (25th August 2022) - Han, Xiaojun; Xu, Yang; Wei, Zhanying; Wang, Chun; Yue, Hua; Zhang, Zhenlin
Abstract: Background: Melorheostosis (MEL) is an exceptionally rare sclerosing bone dysplasia with asymmetrically exuberant bone formation and soft tissue lesions in a segmental distribution. We aimed to summarize the clinical characteristics of Chinese MEL patients and identify their pathogenic cause. Methods: In total, 10 Chinese MEL patients were recruited, and clinical manifestations and radiological characteristics were recorded. Sanger sequencing of the LEMD3 gene was performed on peripheral blood samples of all patients, while the exome sequencing of matched peripheral blood, melorheostotic bone, and skin lesion samples was conducted on one patient who provided affected bone and skin tissues. Micro‐computed tomography (micro‐CT) was also used to scan the melorheostotic bone tissue. Results: We found the average age of the 10 MEL patients was 29.5 years (range 11–40 years), and the major symptoms were bone pain, restricted movement, and bone deformity. The lesions sites were mainly located in femur (8/10), tibia (8/10), fibula (6/10), and foot (7/10), the next was pelvis (4/10), and the last were patella (1/10), hand (1/10) and spine (1/10). Radiological examinations showed a mixture of hyperostosis consisting of classic "dripping candle wax, " "osteoma‐like, " or "myositis ossificans‐like" patterns in most patients. No germline pathogenic variants in the LEMD3 gene were found in all patients, but a disease‐causing somatic variant of MAP2K1 (c.167A > C, p.Gln56Pro) was detected in melorheostotic bone from one patient. Moreover, the micro‐CT analysis showed increased porosity in the melorheostotic bone with somatic MAP2K1 variant. Conclusion: This is a summary of the clinical characteristics of Chinese MEL patients and we first identify the somatic MAP2K1 variant in Chinese patients. Our findings validate the molecular genetic mechanism of MEL and broaden its phenotype spectrum in the Chinese population. Abstract : We investigated ten Chinese patients with melorheostosisdiagnosed with clinical manifestations and typical radiological findings. Through Sanger sequencing on the LEMD3 gene of all the patient's peripheral blood samples and exome sequencing on the biopsied affected bone and skin tissues of one patient, we first identified somatic variant in MAP2K1 in Chinese MEL patients.